An initial investigation to explore the feasibility of fruit waste fillers for developing sustainable thermoplastic composites - Sharma H.; Singh I.; Misra J.P. (My University, 2025)
The current research work is aimed to study the potential of citrus limetta peel (fruit waste) as a novel filler in thermoplastic composites. Three different sizes of citrus limetta peel (CLP) fillers were processed and their thermal characteristics such as thermo-gravimetric analysis (TGA) and derivative thermogravimetry (DTG) were evaluated to investigate the degradation behaviour of each filler size under temperature. FTIR analysis of the CLP was also done to study the structure of inter- and intra-molecular hydrogen bonding in cellulose. The morphological study was also performed on both the outer surface as well as the inner surface of CLP in order to examine the surface characteristics. Based on the thermal characteristics of CLP filler, CLP-filled thermoplastic (poly-lactic acid) composite samples (by 20% weight percentage) were successfully fabricated using the injection moulding technique and were evaluated for their thermal, mechanical, and microstructural behaviour. It has been established that CLP fillers are amenable to processing using closed-mould processes such as injection moulding with fabricated products finding possible application in non-structural products, preferably in the particle board industry. As per the feasibility analysis, CLP fillers have the potential to be commercially exploited for product development. © IMechE 2023.